Reactivation of human immunodeficiency virus type 2 in macaques after simian immunodeficiency virus SIVmac superinfection. - Petry, H (1995)
By superinfection of human immunodeficiency virus type 2 (HIV-2) strain HIV-2ben-infected macaques with simian immunodeficiency virus (SIV) strain SIVmac, we investigated the mutual influences of an apathogenic and a pathogenic virus in vivo. Four rhesus and two cynomolgus monkeys were infected with HIV-2ben in 1988 and 1989, respectively. Virus could be reisolated from five of six animals 6 weeks after infection. The monkeys remained healthy over the next 2 to 3 years. PCR for viral RNA became negative, and virus could no longer be reisolated by coculture. All six macaques were superinfected with the pathogenic SIVmac251/32H. Subsequently, five monkeys became persistently viremic, while one animal was protected against the SIVmac infection. In the peripheral blood mononuclear cells and cocultures of the five viremic animals, DNA from both HIV-2 and SIVmac was present. The plasma contained RNA from both viruses. Thus, superinfection with SIVmac activated HIV-2. A proliferative T-cell response against both HIV-2 and SIVmac was measured in all animals after superinfection. Such a response was regularly seen after infection with the apathogenic HIV-2 but never when the pathogenic SIVmac alone was administered. While naive control monkeys inoculated with SIVmac251/32H regularly develop AIDS-like symptoms soon after infection and have to be killed, none of the preinfected animals has developed AIDS-like symptoms, but two of six animals developed tumors. After the SIVmac challenge, however, apoptotic lymphocytes were detected in the peripheral blood mononuclear cells of all animals. Thus, the presence of an apathogenic viral variant seems to retard the disease occurring after infection with a pathogenic virus rather than to confirm total protection. This partial protection appears to depend on a specific proliferative T-cell response early after infection.